Pengembangan LKPD berbasis Creative Problem Solving (CPS) dengan Pembelajaran Autentik untuk Meningkatkan Creative Thingking Skill - Yeni, Fitra; Djamas, Djusmaini (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This analysis aims to develop learners worksheets based on Creative Problem Solving (CPS) with authentic learning to improve creative thinking skills. The steps of the Creative Problem Solving (CPS) model are 1) Understanding the challenge, 2) Generating ideas, 3) Preparing for action and 4) Planning your approach. In the learning model of Creative Problem Solving (CPS) aims to increase creative thinking skills of learners by using authentic learning. Type of research is developmental research (research and development) using a 4-D model. The research phases are define, design, development and (disseminate). One step in define phase is the learners’ analysis that is limited to creative thinking skills analysis. The respondents selected in this study are students of class X MIPA 3 which consists of 35 students which are in SMAN 2 Padang. The analytical instrument used in this study is by using a questionnaire. Data analysis techniques performed is in the form of scoring using Likert scale. For each item of statement provides 4 (four) alternative answers. Based on the analysis of data that has been done, research results can be stated, that is the average level of Creative Thinking Skills of learners is 48.6%, where 47.4% of learners are able to think fluently ( fluency ) ; 48.3% of learners are able to think flexibly ( flexibility ) ; 45% of learners are able to think originally ( originality ) ; and 53.7% learners are able to think in detail ( elaboration ). Overall, the levelof Creative Thinking Skill of learners is still in the low category. The suggested suggestion based on the result of field study is the condition of the learners is good, by using Creative Problem Solving (CPS) model, it is expected that the learners' learning result can be improved on the harmonic vibration material to improve the creative thinking skill of the learners in authentic learning contained in learners worksheets.